Models for the Diastereoselective Synthesis of Indolizidine Alkaloids: - Krause, Rui Werner Maçedo (My University, 2006)
The synthesis of nitrogen containing ring systems has been one of the interests of this research group at the University of the Witwatersrand for a long time. These systems form part of a group of compounds called alkaloids, whose structural diversity is rivalled only by their distribution in nature. A small sub-set of the alkaloids is the fused 5 and 6 membered bicyclic frames with nitrogen at one bridgehead. Having developed a unique method of synthesising these indolizidine alkaloids, we examined various aspects of this methodology and there remained one crucial question – what is the best way to control the stereochemical outcome of the ring-forming steps? This project looks at this question from the view of a model natural product, the indolizidine alkaloids (+)- and (–)-tashiromine. The synthesis of tashiromine and related compounds was examined using chiral auxiliaries such as the Oppolzer sultam and the Evans oxazolidinone, as well as the use of chirally modified reductants. The efficacies of the chiral auxiliaries were studied using molecular modelling techniques, and certain modifications were suggested from these results.
Faculty of Science; School of Chemistry; PhD Thesis
Keywords: Diastereoselective Synthesis; Indolizidine Alkaloids; alkaloids; bicyclic frames; auxiliaries; tashiromine; chiral